The dichotomy between protection and logging of the Endangered and valuable timber species Amburana cearensis in north-west Argentina - Politi, Natalia (2015)
Amburana cearensis is a commercially valuable timber species, categorized as Endangered on the IUCN Red List. It is distributed throughout the seasonal dry tropical forests of Brazil, Paraguay, Bolivia, Peru and Argentina. In Argentina it is restricted to the provinces of Salta, where legislation sets a minimum cutting diameter of 60 cm, and Jujuy, where logging of this species has been banned since 1972. The effect of these laws on the species' conservation status has not been assessed. We estimated species density, using distance sampling methodology, and measured the diameter at breast height of each individual encountered at 13 sites in north-west Argentina. Across both provinces we found a density of 1.12 individuals ha-1 (95% CI 0.48-2.63) and there was no significant difference between the density in Salta (5.15 ha-1;; 95% CI 3.14-8.45) and that in Jujuy (3.67 ha-1;; 95% CI 2.59-5.17), although 84% of the individuals encountered in Salta were found at one site. Diameter at breast height was significantly lower in Salta than in Jujuy (23 ± 12 vs 41 ± 18 cm; P < 0.05). These differences in the demography of the species between the provinces may be attributable to the application of different legislation. Our results indicate that it would be prudent to halt logging of this species in Salta until further information is gathered and a sustainable management plan developed.